Induction of whole-body gene deletion via R26-regulated tamoxifen-inducible Cre recombinase activity - Kumar, Rahul; Mao, Yun; Patial, Sonika; Saini, Yogesh (Frontiers in Pharmacology, 2022)
Germline deletion of certain genes causes embryonic lethality, therefore, understanding the effect of deletion of such genes on mammalian pathophysiology remains challenging. Tamoxifen (TAM)-inducible Cre recombinase (Cre-ERT2) is widely used for tissue-specific and temporal induction of gene deletion in mice. However, the tamoxifen treatment regimen for the generation of whole-body deletion of a gene is not yet fully standardized for the majority of organs/tissues. Accordingly, we employed GtROSA26 (R26) promoter-regulated Cre and a reporter gene expression strategy. GtROSA26 (R26) is a ubiquitous promoter and mice carrying the R26Cre-ERT2 transgene express Cre-ERT2 in all the cells. Similarly, mice carrying the R26mTOM-mEGFP transgene express mTOM (membrane-targeted tdtomato), in the absence of Cre or mEGFP (membrane-targeted enhanced green fluorescent protein), in the presence of Cre, in all the cells. The progeny carrying one allele of both transgenes were subjected to different TAM regimens, i.e., IP injections (4 injections; 1.35mg/injection), diet (400 mg TAM-citrate/kg food), or diet (400 mg TAM-citrate/kg food) combined with either TAM-oral gavage (4 gavages; 1.35mg/gavage) or TAM IP injections (4 injections; 1.35mg/injection) for 2-weeks beginning at postnatal day 21 and the extent of Cre recombination in different tissues was determined at PND35. Tamoxifen administration resulted in a transient loss of body weight in all the treatment regimens with a relatively slower rate of weight gain in the TAM-diet plus TAM-oral gavage group compared to other groups. While the efficiency of Cre recombination, as determined by the expression of mEGFP protein, was variable among tissues, major tissues such as the liver, heart, lungs, spleen, thymus, and kidney showed almost complete recombination. No recombination was evident in any of the tissues examined from control mice. In general, the efficiency of Cre recombination was better with a combined regimen of TAM-diet with either TAM-injections or TAM-oral gavage compared to TAM-diet alone or TAM-injections alone. Our results demonstrate that a combination of TAM-diet with either TAM-injections or TAM-oral gavage can be employed for the efficient deletion of a gene in the whole body. Our findings will provide technical expertise to the researchers employing TAM-inducible Cre for the deletion of floxed genes in varied tissues.